Inhibition of feline immunodeficiency virus infection by CD9 antibody operates after virus entry and is independent of virus tropism. - Willett, B; Hosie, M; Shaw, A; Neil, J (Journal of General Virology, 1997)
A monoclonal antibody which blocks infection with feline immunodeficiency virus (FIV) was found previously to react with the cell surface molecule CD9, implicating CD9 in the process of virus entry. We report here that inhibition by anti-CD9 antibody does not operate at the level of virus entry but at a subsequent stage in the virus life-cycle. Moreover, inhibition of infection is independent of the passage history of the virus or the virus subtype. Inhibition of FIV infection by anti-CD9 antibody does not operate in 3201 cells, which do not express this surface antigen. However, ectopic expression of CD9 on 3201 cells enhances infection with FIV, suggesting that the role of CD9 may be direct rather than via cellular signalling pathways. These results suggest a novel control point in the lentivirus life-cycle which might be susceptible to modulation by natural antagonists.